CSR Reporting Practices of Hungarian Banks - Horváth, Dóra Diána (International Journal of Engineering and Management Sciences, 2017)
The disclosure of information on the exercise of corporate social responsibility (CSR) is the tool most frequently used by companies to promote understanding of the social and environmental performance of an organisation and to improve relationships with stakeholders. For most of the world’s largest companies, reporting on non-financial information appears to be a continuing trend, so it is essential to present the new corporate reporting trends of the 21st century. The disclosure of socially responsible information will be analysed, with a focus on the application of the Global Reporting Initiative guidelines related to CSR. Global Reporting Initiative (GRI) is the best-known framework for voluntary reporting of environmental and social performance by business worldwide. The main objective of the paper is to explore the corporate voluntary disclosure practices of the listed and non-listed banks in Hungary. The extent of voluntary disclosure has significantly improved for decades worldwide, but the situation is not that obvious regarding the Hungarian financial sector. This paper aims to describe the status of disclosure practices of corporate sustainability in the annual reports, sustainability reports or CSR reports of the banking industry in Hungary. Also, increased corporate visibility and financial risk increase stakeholder demand for transparency on the social impact of financial institutions and their CSR practices. Finally, the analysis and subsequent comparison of available CSR reports of banks will be presented.